2020
DOI: 10.1111/dth.13251
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of isotretinoin: A comprehensive review

Abstract: Isotretinoin is a first‐generation retinoid initially approved for the treatment of severe cases of acne vulgaris (nodulocystic acne). Because of its broad anti‐inflammatory and immunomodulatory properties, it has been used beyond its initial approval in a myriad of other indications. Adverse effects of isotretinoin vary from xerosis to teratogenicity. Herein, we reviewed the literature, through date‐unlimited PubMed search, from inception till December 2019, using the following search terms: “low‐dose isotret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 115 publications
0
14
0
2
Order By: Relevance
“…A study conducted by Karadag et al showed that isotretinoin may lead to a slight reduction in pituitary hormone and testosterone levels [21]. Likewise, Rademaker et al also observed a marked reduction in serum testosterone levels as a result of isotretinoin therapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Karadag et al showed that isotretinoin may lead to a slight reduction in pituitary hormone and testosterone levels [21]. Likewise, Rademaker et al also observed a marked reduction in serum testosterone levels as a result of isotretinoin therapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Isotretinoin with its anti-inflammatory and immunomodulation characteristics has been approved for the treatment of comedonal acne [ 6 ]. The adverse side effects of isotretinoin include but are not limited to rash, teratogenicity and dry mouth [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retinoids are a group of drugs that are derived from vitamin A or are chemically related to it (Abdelmaksoud et al, ; Altıntaş Aykan & Ergün, ; Tugrul Ayanoglu, Demirdag, Yalici Armagan, & Bezirgan, ). Retinoids play a major role in functioning of the body including vision, cell proliferation regulation and differentiation, growth of bones, immunity, and tumor suppressor genes activation (Ahmad, ; Brzezinski, Borowska, Chiriac, & Smigielski, ; On & Zeichner, ).…”
Section: Introductionmentioning
confidence: 99%